Tissue-friendly dentin treatments as a potential element in revascularization protocol (ex-vivo study) - Hala Fayek Khalil; Nadia Ezz El Din Metwalli; Sara Magdy; Mohamed Shamel (BMC Oral Health)
Abstract Background Endodontic treatment aims to eliminate pulp tissue, microorganisms, and toxins while creating an environment conducive to tissue revitalization and regeneration. Sodium hypochlorite, the gold-standard irrigant, is effective but has significant cytotoxic effects, prompting the need for safer alternatives. This study investigates the cytotoxicity, cell proliferation, adhesion to dentin, and osteogenic differentiation of cells exposed to Dual Rinse HEDP, curcumin, and sodium hypochlorite (2.5%) for 1, 5, and 15 min, focusing on their potential application in revitalization and regenerative endodontic protocols. Methodology Samples were assigned to groups based on the irrigant used: control, HEDP, curcumin, or sodium hypochlorite (2.5%) for exposure durations of 1, 5, and 15 min. Cytotoxicity was assessed using the MTT assay, with optical density measured at the specified times. Cell proliferation was evaluated via the Trypan blue exclusion test, with viable cells counted using a hemocytometer. Data were presented as mean and standard deviation (SD) values and statistical significance was set at p < 0.05 for all tests. Cell adherence to dentin discs was analyzed using scanning electron microscopy (SEM) after 5-min irrigant exposure. Osteogenic differentiation was assessed through alizarin red staining for calcium deposition and quantitative PCR analysis of BMP-2, TGF-β1, VEGF, and DSPP gene expression. Results Cell cytotoxicity differed significantly across groups (p < 0.05), with HEDP showing the best results at 1 and 5 min. After 15 min, Group II had the highest value, followed by Group I. HEDP also recorded the highest cell proliferation, followed by curcumin. HEDP exhibited substantial calcium deposition and significantly upregulated BMP-2, TGF-β1, VEGF, and DSPP gene expression, surpassing other materials. Curcumin moderately promoted calcified nodule formation. Osteogenic media also induced significant gene upregulation. Conclusions Dual Rinse HEDP and curcumin are tissue-friendly. Dual rinse HEDP efficiently increases stem cell adherence to dentin discs and their osteogenic differentiation. So, this irrigant has the potential to be used in regeneration protocols.